KONJUNGSI DALAM LIRIK LAGU-LAGU BOB MARLEY AND THE WAILERS PADA ALBUM SURVIVAL - MANARISIP, VIANDO IMANUEL (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research is entitled â€œConjunction in the Album Survival by Bob Marley and The Wailersâ€. Conjunction is a word used to connect words, phrases, and clauses. Conjunction shows the relationship between sentence elements that they connect. The purpose of this research is to describe, identify, and analyze the forms, functions, and meanings of conjunction in the songs of Bob Marley and The Wailers in the Album Survival (1979). The method used in this research is descriptive. The identification and classification of the data are based onÂ Payne (2011) and Algeo (2006) about forms and functions of the conjunction. Furthermore, there is an analysis of the data about meanings of conjunctions follows Hartford (2004) and ABA English (2014). The results show that the conjunctions found in the lyrics of the songs are: coordinate conjunctions and, but, for and coordinate conjunctions complex and then, and subordinate conjunctions are â€˜cause, before, when, as, so, than, that, who, which, what, if, and no matter. The function of the coordinate conjunctions is to connect words, phrases, clauses and sentences, whereas the subordinate conjunctions are to connect clauses. The meaning of the conjunctions is as stated in the concepts used, they are in addition, time, contrast, result, purpose, etc. The investigation has been done through the library and field research. The data about conjunction in the songs are being collected from album Survival (1979) by Bob Marley and The Wailers. It is expected that this study can be continued by students of English Department and those who are interested in learning one of the aspects of English, in this case, conjunctions. ——————————————————————————————————– Key words: Album Survival Bob Marley and The Wailers, Conjunctions, Forms, Functions, Meanings